(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract : The research aims to study the merger of companies and its impact on financial indicators and then on stock prices in the financial markets, as the merger indicates the tendency of two or more companies to create a new entity (the merging company) capable of achieving the company’s objectives and improving financial indicators, which is reflected in stock prices in the market. Finance, and the research sample was the merger of Al-Zawra Springs General Trading and Contracting Company Limited, Real Estate Investments, and Healthy Water Bottling, Soft Drinks, and Juices Company Limited (Aquafina) with the Baghdad Soft Drinks Company in the first phase in 2017, then the merger of the Zaki Group Company for General Trade and Food Industries Limited with the Baghdad Beverages Company. Al-Ghaziyeh in the second phase in 2021, and data and information were collected through the annual financial reports issued by the Iraq Stock Exchange for the time period (2014 - 2022), as well as data from other companies. The financial indicators represented by indicators of liquidity, activity, indebtedness, and profitability were measured, as well as the stock prices of the merging company, Baghdad Soft Drinks Company. As for the analysis process, the program Exel 2013 and SPSS were used, and the arithmetic mean, standard deviation, and variance were measured. The research reached results, the most important of which is the success of the merger operations. For the Baghdad Soft Drinks Company, and there is no discrepancy between the financial indicators before and after the merger, despite the decline in the financial indicators for the Baghdad Soft Drinks Company in the first year after the merger as a result of the significant decline in the indicators before the merger of the merged company, but the indicators begin to improve in subsequent years.